Statistical Analyses for Language Testers - Green, R. author. aut Link
XVI, 310 p.
Keywords: Provides a step-by-step approach to the most useful statistical analyses for language test developers and researchers using IBM SPSS, Winsteps and Facets. It contains clearly-worked out examples for each analysis with detailed explanations.